The hidden costs of working from home: examining loneliness, role overload, and the role of social support during and beyond the COVID-19 lockdown - Fostervold, Knut Inge; Ulleberg, Pål; Nilsen, Odd Viggo; Halberg, Anne Marie (Frontiers in Organizational Psychology, 2024)
Objective This study evaluated the impact of the number of days per week working from home (WFH) on employee loneliness during and 2 years after the COVID-19 lockdown, with a focus on role overload as a mediating factor and social support from coworkers as a moderating variable. Methods Data were collected via self-reports from a sample of 6,918 participants during the lockdown in January 2021 and 6,576 participants 2 years post-lockdown in January 2023. Results Analysis using a moderated mediation model showed that increased WFH days were associated with heightened loneliness during the lockdown, a link that weakened post-lockdown. Role overload served as a mediator, intensifying loneliness during WFH but less so after the lockdown. While higher social support was generally linked to reduced role overload and loneliness, it paradoxically intensified these issues in individuals with extensive WFH days. Conclusions The findings suggest that the number of days WFH can exacerbate loneliness and role overload among employees, with the effect being more pronounced during the lockdown. Employees with substantial social support faced more challenges as WFH duration increased. These results underscore the complex dynamics between WFH, social support, and employee wellbeing.